Chemokine ligand 2 and paraoxonase-1 in non-alcoholic fatty liver disease: The search for alternative causative factors - Camps, Jordi (World J Gastroenterol, 2015)
The incidence and prevalence of non-alcoholic fatty liver disease (NAFLD) is constantly increasing. Despite this is apparently associated with the growing increase in obesity, insulin resistance and obesity-related metabolic disturbances their presence is not a necessary or sufficient condition to explain the accumulation of fat in the liver. Conversely, NAFLD is a predictor of other metabolic risks. NAFLD is currently the most frequent chronic liver disease but should not be considered benign or anecdotic because a considerable proportion of patients with NAFLD progress to cirrhosis and end-stage liver disease. Consequently, the search for alternative molecular mechanisms with therapeutic implications in NAFLD and associated disorders deserves a careful consideration. Mitochondria are possible targets as these organelles generate energy from nutrient oxidation. Some findings, generated in patients with extreme obesity and in murine models, support the notion that NAFLD could be a mitochondrial disease. This is plausible because mitochondrial dysfunction affects the accumulation of lipids in hepatocytes and promotes lipid peroxidation, the production of reactive oxygen species, the release of cytokines causing inflammation and cell death. Here we discuss basic research and mechanistic studies targeting the role of chemokine ligand 2 in liver inflammation and that of the paraoxonases in the oxidative stress. Their combination and association with mitochondrial dysfunction may uncover mechanisms underlying the progression of NAFLD and may help to identify novel therapeutic targets.